Mediadores cognitivos e emocionais de problemas de conduta e traços Callous-unemotional no desenvolvimento infantil - Silva, Roberta Salvador (2018)
This thesis aimed to investigate callous-unemotional traits and possible mediators in the early stages of development. Thus, a longitudinal study was carried out, with 457 children between six and seven years old followed for two years. This longitudinal study resulted in two empirical studies. The first study aimed to investigate the impact of callous-unemotional traits (CU) in the emotional faces recognition using brief stimuli duration. The results showed that children with CU had higher rates of conduct problems and deficits in the recognition of fear in T2 and sadness in T1 and T2. The deficits were more accentuated with shorter stimulus duration. Moreover, CU group were the only one not to show improvement in the accuracy of these emotions during the follow-up. The second study aimed to investigate the association between callous-unemotional traits and cognitive empathy as predictors of the severity of conduct problems throughout development. It was identified that children with CU presented impairment in cognitive empathy. Furthermore, a hierarchical regression shows that cognitive empathy was a predictor of more severe behavioral problems throughout development. The results of this study may contribute to the development of an early intervention focused on the emotional recognition training, aiming for greater effectiveness than the current treatment protocols focused on the behavioral consequences, currently ineffective for CU traits.